Locating the Atrocities Against Dalits: An Analytical Approach. Issue 1 (May 2020) - Prasad, Devi; Bibhar, S. S.
Dalits constitute around a sixth of India's population. They have been safeguarded by the 'Scheduled Castes and Scheduled Tribes (Prevention of Atrocities) Act, 1989', but the adequate implementation of this special Act is in question because many instances of atrocities have been occurring consecutively. As such, this article attempts to understand the process of building a social milieu for preventing the atrocities against Dalits with particular reference to the Ganda caste. The primary data have been collected through personal narratives of the survivors along with group discussions with the villagers of Lathor in Balangir district of Odisha. Secondary sources such as Indian census reports, newspapers, websites and various constitutional provisions have also been referred to obtain an in-depth understanding of the atrocities against this marginal section.